2021
DOI: 10.1111/jop.13139
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Photodynamic therapy in oral premalignant and malignant lesions: A systematic review

Abstract: Background Photodynamic therapy (PDT) is considered as a valid treatment option in various branches of dentistry. This systematic review aims to evaluate the usefulness of PDT for treatment of oral premalignant and malignant lesions. Methods The MeSH terms “Photodynamic therapy” and “PDT,” in combination with other terms, have been searched by three search engines (PubMed, ISI Web of Science, and the Cochrane Library), and a systematic review has been performed. The Population, Intervention, Comparison, Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…The direct method involves high-energy photons directly damaging vital parts of bacterial cells, while the indirect antimicrobial PDT can be described as an oxygen-dependent photochemical reaction generated by the activation of a PS through a light source. The combination of a non-toxic PS, visible light with appropriate wavelength and oxygen leads to the production of highly reactive and cytotoxic ROS (singlet oxygen), consequently destroying cells [63][64][65][66][67][68]. The randomized controlled split-mouth clinical trial by Birang et al [69] evaluated the role of adjunctive PDT in patients suffering from chronic periodontitis, highlighting significant short-term improvements (three months follow-up) in terms of bacterial count, CAL, and PD.…”
Section: Discussionmentioning
confidence: 99%
“…The direct method involves high-energy photons directly damaging vital parts of bacterial cells, while the indirect antimicrobial PDT can be described as an oxygen-dependent photochemical reaction generated by the activation of a PS through a light source. The combination of a non-toxic PS, visible light with appropriate wavelength and oxygen leads to the production of highly reactive and cytotoxic ROS (singlet oxygen), consequently destroying cells [63][64][65][66][67][68]. The randomized controlled split-mouth clinical trial by Birang et al [69] evaluated the role of adjunctive PDT in patients suffering from chronic periodontitis, highlighting significant short-term improvements (three months follow-up) in terms of bacterial count, CAL, and PD.…”
Section: Discussionmentioning
confidence: 99%
“…A variant of AF is fluorescence induced by exogenous fluorophores, such as toluidine blue or 5-amino-laevulinic acid [125]. In these cases, exogenous fluorophores are not only used for diagnostic purposes but also for low-dose laser therapy techniques such as photodynamic therapy (PDT), which is a minimally invasive treatment for malignant and premalignant lesions, previously diagnosed by conventional biopsy, according to the selective destruction of only cells that retain fluorophores topically administered to the dysplastic/neoplastic lesion [126][127][128][129][130][131].…”
Section: Discussionmentioning
confidence: 99%
“…Topical PDT using 5-aminolevlunic acid and either laser or LED light source has demonstrated good results in small studies [90,91] and a recent systematic review of 27 relevant studies concluded that PDT appears to offer advantages for oral potentially malignant lesions refractory to other treatments. In addition, side effects of topical PDT are mild and it remains an option for patients who refuse traditional surgical interventions [92]. LightOx, a commercial partnership invested in developing light-based therapies for oral cancer, have developed a novel class of small-molecule, topically applied therapies, with phototoxic properties combined with hydroxamic acid to increase solubility [93].…”
Section: Photoactivated Therapymentioning
confidence: 99%